Evaluación y reducción de los niveles de cromo en muestras de aguas residuales provenientes de curtiembres (2016)
Chromium is a dangerous element which is transported in the water and might be absorbed through the consumption of water and food by plants and animals. This element generates harmful effects like genetic, mutagenic and carcinogenic when it enters the organisms by ingestion or inhalation. Therefore, the high levels of chromium in the waste water generated in tanneries represent a risk for the living organisms. This paper shows the advances of a current research related to the evaluation of the levels of chromium in samples of waste water from tanneries. An alternative to reduce the chromium content in the waste water is proposed by using lime. Also, the effects of orange peel in the chromium reduction are evaluated. The results from this research can be taken as a benchmark for the construction of wastewater treatment plants in which new alternatives for the chromium reduction can be implemented, and in consequence, a decrease in the negative effects of this metal in the water resources.